Effects of antiproteolytic agents on corneal epithelial viability and matrix metalloproteinase-2 and metalloproteinase-9 activity in alkali-burned corneas of rats - Trujillo Piso, Dunia Y. [UNESP]; Ribeiro, Alexandre P.; Silva, Miguel L. [UNESP]; Guimaraes, Patricia J. [UNESP]; Morales, Adriana [UNESP]; Martins, Bianca C. [UNESP]; Padua, Ivan M. [UNESP]; Renzo, Roberta [UNESP]; Andrade, Alexandre L. [UNESP]; Uscategui, Ricardo R. [UNESP]; Laus, Jose L. [UNESP] (Wiley-Blackwell, 2014)
Objective To evaluate the effects of agents on corneal re-epithelization and metalloproteinase-2 and metalloproteinase-9 (MMP-2 and MMP-9) activities in corneas of rats submitted to ulceration.Animals Studied Ninety eight healthy rats.Procedures Corneal ulcers were created using 1N NaOH in their left eye. Eyes were treated every 6 h with 1% ethylenediaminetetraacetic acid (EDTA), 3% chondroitin sulfate (CS), 10% N-acetylcysteine NAc and saline (S) at 6-h intervals. Corneas were stained with fluorescein and photographed at the same time points. Following 20 h and 40-42 h of corneal injury, corneas were processed for scanning electron microscopy (SEM) to quantify microvilli density, and MMPs activities were analyzed using zymography.Results The percentage of wound area and the time in hours for corneal re-epithelization did not differ significantly among treatment groups (P > 0.05). In first and the second moments, latent MMP-2 was significantly elevated in the eyes treated with NAC and CS (P < 0.001). Active MMP-2 did not change significantly among treatment groups in the first moment (P > 0.05); significantly higher activity was observed in the second moment in the eyes treated with CS (P < 0.001). In the second moment, latent MMP-9 decreased significantly in eyes treated with EDTA and S (P < 0.01). Microvilli corneal density did not change significantly between healthy subjects and treatment groups (P > 0.05).Conclusion Any of the studied substances did not accelerate corneal re-epithelization and did not add protection to the corneal microvilli. Significant higher levels of active form of MMP-2 in 3% chondroitin sulfate-treated group may indicate that the agent acts as substrate for such enzyme. At the end of the experiment, 1% EDTA was the most efficient agent to inhibit significantly the latent form of MMP-9. However, any of the substances add benefit over saline on reducing the proteolytic activity in the cornea of rats after alkali injury.
Keywords: Cornea; metalloproteinases; Rat; ulcerative keratitis